The Impact of Digital Technological Advances on Human Life: A Review of Educational, Social, Economic, and Security Aspects - Izzatul Zilla Fauza; Helmi Alreza; Mahdatul Maesiyah; Firdanis Tsaqif Yumna; Zidni Rahmatika Maulidah; Meisya Fara Dania; Ida Fatus Salamah; Arif Widagdo (Anthroposia: Journal of Social and Human Development, 2026)
Digital technological advancement has fundamentally transformed various dimensions of human life, including education, social interaction, economic activities, and information security. This study aims to examine the positive and negative impacts of digital technology through a descriptive-analytical literature review approach. Data were collected from academic journals, books, institutional reports, and other relevant scholarly publications. The findings indicate that digital technology contributes to broader access to information, supports flexible online learning, enhances communication efficiency, promotes the growth of e-commerce, facilitates the digitalization of micro, small, and medium-sized enterprises, and creates new employment opportunities. At the same time, digital transformation generates several challenges, including gadget dependency, cyberbullying, reduced face-to-face interaction, misinformation, cybercrime, and risks related to personal data misuse. The review highlights that the effects of digital technology are multidimensional and depend on how technology is utilized, regulated, and integrated into society. Strengthening digital literacy, cybersecurity measures, and collaborative governance is essential to maximize the benefits of digital transformation while mitigating its associated risks.